Measurements in spine care - Chapman, Jens R (AOSpine ; Thieme [distributor], 2012)
In the course of evaluating the patient with spinal disease, a myriad of measurements need to be performed before determining the diagnosis and the severity of the disease process. This text explicitly outlines the measurement of the spine from a clinical, laboratory, and radiographic approach. A detailed description of the actual technique of measurement and the clinical implication are presented with accompanying illustrations. This amalgamation of measurement tools for the spine is a beneficial reference for a wide spectrum of healthcare providers: students, nurses, residents, fellows, and established surgeons.